At the mountains of madness - Lovecraft, H. P. (Howard Phillips), 1890-1937; Brown, Howard V., 1878-1945 (Salt Lake City, UT : Project Gutenberg, 2023)
"At the mountains of madness" by H. P. Lovecraft is a science-fiction and cosmic horror novella written in 1931 and published in 1936. The story follows Dr. William Dyer as he recounts a catastrophic Antarctic expedition in 1930, hoping to prevent future explorers from returning. His team discovers an ancient alien civilization predating humanity, preserved ruins beyond towering mountains, and prehistoric creatures that defy classification. As they uncover the terrifying history of Earth's original inhabitants through ancient murals, they encounter something far more dangerous lurking in the frozen wasteland. (This is an automatically generated summary.)
Wikipedia page on this work: https://en.wikipedia.org/wiki/At_the_Mountains_of_Madness
Release date is 2023-04-27
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Fantasy fiction; Horror tales; Antarctica -- Fiction; Fossils -- Collection and preservation -- Fiction; Scientific expeditions -- Fiction; Stone carving -- Fiction